Data-driven virtual engine framework for predicting performance and emissions of biomass waste-derived biofuel engine - R. Anita Jasmine; D. Jesu Godwin; Edwin Geo Varuvel; J.S. Femilda Josephin; Farzad Kiani; Jonas Matijošius; Tadas Žvirblis; Artūras Kilikevičius (Biomass and Bioenergy, 2027)

What determines trophic niche breadth? A global analysis of freshwater fishes using isospaces - Friedrich Wolfgang Keppeler; Tommaso Giarrizzo; Carmen G. Montaña; Alphonse Adite; Şenol Akın; Ronaldo Angelini; Caroline C. Arantes; Evanilde Benedito; Thethela Bokhutlo; Rana El-Sabaawi; Alexandre Garcia; Ivan Gonzalez-Bergonzoni; et al. (Reviews in Fish Biology and Fisheries, 2026)

Target-site resistance genotype impacts temperature-dependent pyrethroid toxicity in Aedes aegypti - Kendra A. Dagg; Alden S. Estep; Muhammad Farooq; Whitney A. Qualls; Edwin R. Burgess (Pesticide Biochemistry and Physiology, 2026)

Assessment of RV systolic function by tissue motion annular displacement in healthy cats - Edwin F. Buriticá; Giovana L. R. Tuleski; Vinícius B. C. Silva; Joelma F. Santos; Marlos G. Sousa (Veterinary Research Communications, 2026)

Synthesis, antibacterial activity and molecular docking studies of foetidumin A derivatives - Fadil Y. Nankam; Hermine W. Nono; Arno R. D. Nanfack; Michael H. K. Kamdem; Elodie G. Matheuda; Ervira K. Djoukam; Marthe C. D. Fotsing; Edwin M. Mmutlane; Xavier Siwe Noundou; Vincent P. N. Nziko; Maurice D. Awouafack; Derek T. Ndinteh; et al. (Natural Product Research, 2026)

An integrated approach identifying seasonal variation in allergenic grass pollen in southern Australia - Josh Boyte; Sarah M. Sherson; Lachlan Tegart; Nithya Fernandopulle; Hee Sung Kang; Edwin R. Lampugnani; Jonathan Pham; Graham A. Mackay; Edward J. Newbigin; John F. Golz (Environmental Research, 2026)

Light impacts feeding activity by brown marmorated stink bug on ‘Pinot noir’ grapes - Edwin T. Harris; Erika A. Maslen; Luca Rossini; Serhan Mermer; Nik Wiman; Kyoo R. Park; Vaughn M. Walton (Journal of Pest Science, 2026)

Toxicity and electrophysiological investigation of the phenylpyrazole ethiprole against the house fly, Musca domestica - Shova Mishra; Sarah E. McComic; Oshneil S. Baker; Daniel R. Swale; Edwin R. Burgess (Pesticide Biochemistry and Physiology, 2026)

Paleoenvironments of the Late Quaternary Tonica thermokarst lake, northeastern Illinois, USA, and an extinct elk‐moose ( Cervalces ) - Russell W. Graham; Robert E. Warren; Edwin R. Hajic; Terrence J. Frest; Donald P. Schwert; Jacqueline A. Ferguson; Melissa I. Pardi; Eric C. Grimm; Frances B. King (Journal of Quaternary Science, 2026)
The Tonica Depression (TD), a late Quaternary sediment‐filled basin in northeastern Illinois, formed as a thermokarst lake as evidenced by a basal trash layer, its depositional history, and its occurrence on a late‐Pleistocene permafrost landscape. Stratigraphy and radiocarbon ages reveal that a multiproxy paleoenvironmental record extends throughout the late Wisconsin. Burning of organically enriched sediments has abbreviated the Holocene sequence. The lowest stratum is a glacial diamicton that forms the basin's floor, and at a slightly higher elevation, the rim. Lithofacies 1, supraglacial and debris flow deposits, are draped by undated Peoria Silt (PS). PS yielded molluscs and Coleoptera indicative of spruce forest ( Picea ) in a cold and harsh climate. Lithofacies 2 (ca. 17 500–18 500 cal yr BP) is a “trash zone” with white spruce ( Picea glauca ) wood, cones and needles with pollen, Coleoptera, molluscs, and vertebrates, including an elk‐moose. A “marl,” Lithofacies 3 (ca. 14 600–17 400 cal yr BP), attests to the deepening of the lake (>2 m) as also reflected by the molluscs, coleoptera, and pollen. The environment was an open spruce forest, but the climate was warmer than the previous ones. The top of this zone is composed of a brick‐red deposit with burned organic matter. Lithofacies 4 (ca. 14 600 cal yr BP) is composed of organic silt and lacustrine organic silt: a peaty silt loam. Finally, Middle Archaic artifacts on the rim of TD document human settlement around the depression during the dry and warm Middle Holocene (ca. 6747 cal BP). Tonica is the first well‐studied thermokarst lake from temperate latitudes in the United States, and it provides an excellent paleoenvironmental record of the late Pleistocene of north central Illinois.

Unraveling cellular longevity pathways in poultry under heat stress: functional and computational characterization of the adaptogenic formulation Phytocee™ - K. Shamana; R. Edwin; S. P. Jaishree; D. Prashanth; G. Aboli; M. Deepak (In Silico Pharmacology, 2026)

Unpacking drivers of heterotrophic N2 fixation across aquatic redox gradients: A mathematical model with bioenergetic and stoichiometric constraints - Corday R. Selden; Rebecca A. Everett; Halvor M. Halvorson; Megan E. Berberich; Luca Schenone; Angela Peace; Renn Schipper; Edwin Cruz-Rivera; James Powell; Keisuke Inomura; Robinson W. Fulweiler; Amy M. Marcarelli; et al. (Ecological Modelling, 2026)

Barcoding‐Inferred Biodiversity of Shallow‐Water Indo‐Pacific Demosponges - Dirk Erpenbeck; Adrian Galitz; Michael L. Berumen; Gabriele Büttner; Cécile Debitus; Moritz Dirnberger; Merrick Ekins; Kathryn Hall; Leonard Namuth; Sylvain Petek; Neda Rahnamae; Maggie M. Reddy; et al. (Journal of Biogeography, 2026)
Aim The Indo‐Pacific is the world's largest marine biogeographic region. It is characterised by different degrees of connectivity among its subregions and harbours the majority of demosponge species currently known to science. Comparisons between regional sponge faunas have been undertaken in the past, mostly based on morphological species identification. The Sponge Barcoding Project, in tandem with regional DNA taxonomy campaigns, provides one of the largest DNA‐based taxonomic data collections from sponges of the Indo‐Pacific. Here, we utilise the barcoding data in the most extensive molecular biodiversity study of sponges to date, which reveals patterns of shallow‐water demosponge faunal connectivity, endemism and distribution in the Indo‐Pacific with a level of resolution unavailable in prior morphology‐based studies. Location Demosponge specimens in this study cover 13 marine provinces (MPs) of the Indo‐Pacific. Methods We classified demosponge barcodes from 1910 sponge samples into 701 molecular operational taxonomic units (MOTUs) using 28S rRNA. MOTU composition of the MPs was compared based on Jaccard and Sørenson dissimilarities and other biodiversity indices. Results Our data corroborated high endemism in MPs (up to 84.1% endemic MOTUs). Faunal overlaps are between the Red Sea and the Gulf, which displayed small connectivity with other MPs in the Western Indian Ocean. The Western Indian Ocean is a strong faunistic boundary to the Central Indo‐Pacific, to which the Polynesian sponge faunas were comparatively isolated as well. Main Conclusions Our data corroborate case studies on sponges that generally reject the presence of cosmopolitan or otherwise widespread sponge species, instead revealing high levels of regional endemism. This is consistent with similar observations and hypotheses in other marine invertebrates, and highlights the need for close regional monitoring to identify biodiversity changes. Connectivity among Indo‐Pacific MPs differs for demosponges in many aspects from that of other marine taxa, hypothetically due to their shorter pelagic larval phase.

Redescription of subgenus Persis (Eritalaena) (Hemiptera: Fulgoromorpha: Derbidae), and new occurrence records from the Neotropical Region - Inezita Cantanhede; Eduarda Fernanda Gomes Viegas; Brian W. Bahder; Charles R. Bartlett; Edwin A. Barrantes Barrantes; Marco A. Zumbado Echavarria; Rosaly Ale–Rocha (Biologia, 2026)
Persis ( Eritalaena ) Fennah, 1952 is a monotypic subgenus comprising the species Persis ( Eritalaena ) fuscinervis Muir, 1918, originally described from Guyana (South America). In this study, we redescribe the genus and its sole species, incorporating additional diagnostic characters. We also provide, for the first time, photographs and detailed illustrations of the morphology of both males and females, and we expand the known distribution of the group with new records from Central America (Costa Rica) and South America (Brazil).

Integrated aquatic resource management using GIS: a case study on saltwater intrusion and aquaculture site delineation in Chalakkudy river basin and adjacent Wetlands, South West India - John Anu; P. Minu; S. R. Regi; N. L. Edwin; M. P. Prabhakaran (Wetlands Ecology and Management, 2026)

Cytotoxic prenylated xanthone derivatives from the twigs of Garcinia cowa - Edwin R. Sukandar; Kitiya Rassamee; Pongpun Siripong; Sutin Kaennakam (Natural Product Research, 2026)

Exhaled CO2 and aerosol dispersion on a cruise ship: Airflow and infection risk insights - Sarkawt Hama; Prashant Kumar; Ho Yin Wickson Cheung; Ana Paula Mendes Emygdio; John Ewer; Zhaozhi Wang; Edwin R. Galea; Angus Grandison; Fuchen Jia; Niko Siilin; Pierfrancesco Lepore (Science of The Total Environment, 2026)

Optimizing machine learning models for cytotoxicity prediction in lanthanide-doped nanomaterials: A data-driven approach for minimizing environmental hazards - Edwin E. Reza-Zaldívar; Jorge L. Mejía-Méndez; Diego E. Navarro-López; A. Sanchez-Martinez; O. Ceballos-Sanchez; Vicente Rodríguez-González; Miriam Irene Jiménez-Pérez; L. Marcelo Lozano; Juan Armendariz-Borunda; Daniel A. Jacobo-Velázquez; Gildardo Sanchez-Ante; Edgar R. López-Mena (Journal of Hazardous Materials, 2025)

Understanding and predicting the geographic distributions of phlebotomine sand flies in and around Europe - Danyang Wang; Anouschka R. Hof; Kevin D. Matson; Frank van Langevelde; Vít Dvořák; Ognyan Mikov; Ivelina Katerinova; Simona Tchakarova; Maria Antoniou; Jorian Prudhomme; Denis Sereno; Baptiste Vergnes; et al. (Climatic Change, 2025)
Climate and land-use changes influence the transmission of vector-borne diseases by affecting the distribution and survival of disease vectors. Numerous diseases are transmitted by phlebotomine sand flies (Diptera: Psychodidae: Phlebotominae), including leishmaniasis. Several major sand fly-borne diseases are responsible for high global disease burdens and high socio-economic costs. In Europe, over 20 known sand fly vector species are largely confined to the Mediterranean Basin, yet records of sand fly presence further north increase. Global warming is predicted to drive the spread of sand flies to large areas of Europe in the 21th century, an effect likely to be exacerbated by anthropogenic factors. However, the constraints to the geographic distributions of sand flies are not well understood. This study aims to increase the understanding of the drivers of the geographic distributions of sand flies, using species distribution modelling to systematically test links between sand fly occurrences and climatic, land-use, lithological, biodiversity and human population variables in Europe and adjacent Mediterranean regions. We found that moisture is the most important environmental variable both in explaining and in predicting sand fly occurrences. The projected suitable habitats are larger than the current known sand fly distributions, and these habitats are expected to expand due to changes in climate and land-use.

The discovery and preclinical pharmacology of JNJ-10450232 (NTM-006), a centrally penetrant, non-opioid structural analog of acetaminophen with comparable analgesic and anti-pyretic properties but no evidence of hepatotoxicity - Christopher M. Flores; John R. Carson; Ellen E. Codd; Scott L. Dax; Edwin K. Kuffner; Paul L. Stahle; Robert A. Neff; Gary E. Eichenbaum (Regulatory Toxicology and Pharmacology, 2025)

How does topography affect wind abrasion on Mars? Recently observed shifts in ventifact orientation at Gale crater - Daniel Y. Zhou; Madison L. Turner; William Rapin; Juergen Schieber; Amelie L. Roberts; Aster C. Cowart; Megan E. Hoffman; Bernard Hallet; Steve G. Banham; Deirdra Fey; Kevin W. Lewis; Sanjeev Gupta; et al. (Icarus, 2025)

Optimized modified single shot multibox detector with hybrid encryption algorithm for satellite image security and classification - J. Jeno Jasmine; S. Edwin Raja; R. Muniraj; M. Ulaganathan (Earth Science Informatics, 2025)

Nutritional Quality and Safety of Windowpane Oyster Placuna placenta from Samal, Bataan, Philippines - Jessica M. Rustia; Judith P. Antonino; Ravelina R. Velasco; Edwin A. Yates; David G. Fernig (Fishes, 2025)
The windowpane oyster (Placuna placenta) is common in coastal areas of the Philippines, thriving in brackish waters. Its shells underpin the local craft industries. While its meat is edible, only small amounts are consumed locally, most going to waste. Utilization of this potential nutrient source is hindered by the lack of information concerning its organic and mineral content, the possible presence of heavy metal ions, and the risk of microbial pathogens. We report extensive analysis of the meat from Placuna placenta, harvested during three different seasons to account for potential variations. This comprises proximate analysis, mineral, antioxidant, and microbial analyses. While considerable seasonal variation was observed, the windowpane oyster was found to be a rich source of protein, fats, minerals, and carbohydrates, comparing well with the meats of other shellfish and land animals. Following pre-cooking (~90 °C, 25–30 min), the standard local method for food preparation, no viable E. coli or Salmonella sp. were detected. Mineral content was broadly similar to that reported in fish, although iron, zinc, and copper were more highly represented, nevertheless, heavy metals were below internationally acceptable levels, with the exception of one of three samples, which was slightly above the only current standard, FSANZ. Whether the arsenic was in the safer organic form, which is commonly the case for shellfish, or the more toxic inorganic form remains to be established. This and the variation of arsenic over time will need to be considered when developing food products. Overall, the meat of the windowpane oyster is a valuable food resource and its current (albeit low-level) use should lower any barriers to its acceptance, making it suitable for commercialization. The present data support its development for high-value food products in urban markets.

Removal of PFAS and pharmaceuticals from municipal wastewater using a novel β-cyclodextrin adsorbent over distinct contact times - Emma F. Shapiro; Zhi-Wei Lin; Edwin Saavedra Cifuentes; Francisco J. Barajas-Rodriguez; Rosa Gwinn; William R. Dichtel; Aaron I. Packman (Water Research, 2025)

Carrier solvent effects on the toxicity and penetration rate of fluralaner in the house fly, Musca domestica L. (Diptera: Muscidae) - Joshua Weston; Oshneil S. Baker; Caitlin E. Taylor; Mba-Tihssommah Mosore; Jeffrey G. Scott; Jeffrey R. Bloomquist; Edwin R. Burgess (Pesticide Biochemistry and Physiology, 2025)

Optimized biodiesel production from Java olive seeds using a novel magnetic nanobiocatalyst and advanced optimization techniques - L.R. Monisha Miriam; Ajith J. Kings; Jain B. Marshel; R. Edwin Raj; S. Indran; D. Divya (Biomass and Bioenergy, 2025)

Fish consumption advice is depriving children of neurolipids and other nutrients essential to brain and eye development - Philip Spiller; J. Thomas Brenna; Susan E. Carlson; Jean Golding; Michael A. Crawford; Joseph R. Hibbeln; Berthold V. Koletzko; John Columbo; Penny Kris-Etherton; Sonja L. Connor; Clark Carrington; P. Michael Bolger; et al. (NeuroToxicology, 2025)

Airborne pathogen monitoring and dispersion modelling on passenger ships: A review - Prashant Kumar; Sarkawt Hama; Ho Yin Wickson Cheung; Christos Hadjichristodoulou; Varvara A. Mouchtouri; Lemonia Anagnostopoulos; Leonidas Kourentis; Zhaozhi Wang; Edwin R. Galea; John Ewer; Angus Grandison; Fuchen Jia; et al. (Science of The Total Environment, 2025)

Setting the limit: cold rather than hot temperatures limit intertidal distribution of a coastal foundation species - Kerstin Wasson; Kim Cressman; Kathryn Beheshti; Erin C. Herder; Charlie Endris; Christopher D.G. Harley; Alicia Abadía-Cardoso; Rodrigo Beas-Luna; Joachim Carolsfeld; Andrew L. Chang; Jeffrey A. Crooks; Matthew C. Ferner; et al. (Marine Environmental Research, 2025)

Altered cytokine release of airway epithelial cells in vitro by combinations of respiratory syncytial virus, Streptococcus pneumoniae, Printex 90 and diesel exhaust particles - Marcia M. Oldenburger; Raiza Hasrat; Axel A. Bonacic Marinovic; Eric R. Gremmer; Edwin P. Zwart; Gabriel Goderski; Geraly Duijm; Debby Bogaert; Adam Meijer; Arno Swart; Flemming R. Cassee; Gerco den Hartog; et al. (Environmental Research, 2025)

Two new rotenoid glycosides from the rhizomes of Stemona curtisii Hook. f - Olusola Idowu; Edwin R. Sukandar; Duy Vu Nguyen; Fadjar Mulya; Vudhichai Parasuk; Piyanuch Wonganan; Warinthorn Chavasiri; Pattara Thiraphibundet (Natural Product Research, 2025)

Unveiling the key toxicity indicators and mechanisms on phytotoxicity of cerium dioxide nanoparticles in rice (Oryza sativa) - Rekha Chandran Prasanna Ramachandran; Gauri Santhoshkumar Sreedevi; Boby T. Edwin; Shajesh Palantavida; Mangalaraja R. Viswanathan; Anas Shereef (Chemosphere, 2025)

Influence of ENSO, droughts, and temperature rise on pollen and pollen seasons in Australia - Arzoo Dhankhar; Darsy Darssan; Sagnik Dey; Edwin R. Lampugnani; Simon Haberle; Connie Katelaris; Pamela Burton; Usha Nattala; Nicholas J. Osborne (Science of The Total Environment, 2025)

Mode of toxicity of the β-triketone leptospermone to Aedes aegypti mosquitoes - Sarah E. McComic; Rui Chen; Shova Mishra; Werner J. Geldenhuys; Charles L. Cantrell; Edwin R. Burgess; Troy D. Anderson; Daniel R. Swale (Pesticide Biochemistry and Physiology, 2025)

Emission analysis of combustion of cashew nutshell biodiesel in a toroidal combustion chamber: an experimental study - S. Seetharaman; S. Thiagarajan; V. Sugendrabalaji; P. R. Kumar; R. PraveenKumar; Femilda Josephin Joseph Shobana Bai; Sulaiman Ali Alharbi; A. Pugazhendhi; Edwin Geo Varuvel (International Journal of Environmental Science and Technology, 2025)

Green Technologies for Environmental Air and Water Impact Reduction in Ships: A Systematic Literature Review - Edwin Paipa-Sanabria; Daniel González-Montoya; Jairo R. Coronado-Hernández (Journal of Marine Science and Engineering, 2025)
This study reviews various green technological strategies integrated into vessels to mitigate environmental impact, focusing on atmospheric pollution and marine environment protection. The research is based on a systematic review of academic literature published between 2019 and 2024, using the Scopus and Web of Science databases and applying PRISMA criteria. The findings reveal that the main environmental issues in the naval sector include greenhouse gas emissions, harmful discharges, and invasive species that affect marine biodiversity. The analysis is framed within international regulations such as those established by the IMO and classification societies, where the most relevant indicators identified are the EEDI and EEXI. However, the results of this review emphasize that, while these regulations are fundamental, it is necessary to analyze further the technical and economic barriers affecting the widespread implementation of these technologies and develop incentive mechanisms that facilitate their adoption across different vessel types and sizes. Promising solutions include alternative fuels, new propulsion systems, and emission-reduction technologies. The conclusion underlines that although the sector is transitioning toward sustainability, economic and widespread implementation challenges remain.

Spatial and temporal optimization of potato planting based on on-farm collected data and field experiments - Puck J.A.M. Mulders; Menno J.T.C. van Zutphen; Arie P.P. Ravensbergen; A.T.J.R. Cobbenhagen; Edwin R. van den Heuvel; M.J.G. van de Molengraft; Pytrik Reidsma; Duarte Guerreiro Tomé Antunes; W.P.M.H. Heemels (Agricultural Systems, 2025)

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Evaluation of Reservoir Porosity and Permeability from Well Log Data Based on an Ensemble Approach: A Comprehensive Study Incorporating Experimental, Simulation, and Fieldwork Data - Edwin E. Nyakilla; Sun Guanhua; Hao Hongliang; Grant Charles; Mouigni B. Nafouanti; Emanuel X. Ricky; Selemani N. Silingi; Elieneza N. Abelly; Eric R. Shanghvi; Safi Naqibulla; Mbega R. Ngata; Erasto Kasala; et al. (Natural Resources Research, 2025)

Monitoring of indoor air quality at a large sailing cruise ship to assess ventilation performance and disease transmission risk - Ho Yin Wickson Cheung; Prashant Kumar; Sarkawt Hama; Ana Paula Mendes Emygdio; Yingyue Wei; Lemonia Anagnostopoulos; John Ewer; Valerio Ferracci; Edwin R. Galea; Angus Grandison; Christos Hadjichristodoulou; Fuchen Jia; et al. (Science of The Total Environment, 2025)

A comparative analysis of advanced machine learning models for the prediction of combustion, emission and performance characteristics using endoscopic combustion flame image of a pine oil–gasoline fuelled spark ignition engine - D. Jesu Godwin; Edwin Geo Varuvel; M. Leenus Jesu Martin; Anita Jasmine R; Femilda Josephin JS (Journal of Cleaner Production, 2024)

Interpreting the spatial distribution of soil properties with a physically-based distributed hydrological model - Zamir Libohova; Marcelo Mancini; H. Edwin Winzeler; Quentin D. Read; Ning Sun; Dylan Beaudette; Candiss Williams; Joshua Blackstock; Sérgio H.G. Silva; Nilton Curi; Kabindra Adhikari; Amanda Ashworth; et al. (Geoderma Regional, 2024)

Differential interactions of ethacrynic acid and diethyl maleate with glutathione S-transferases and their glutathione co-factor in the house fly - Edwin R. Burgess; Shova Mishra; Xin Yan; Zhongwu Guo; Christopher J. Geden; Jon S. Miller; Michael E. Scharf (Pesticide Biochemistry and Physiology, 2024)

Isolation and characterization of the decreased cuticular penetration mechanism of fluralaner resistance in the house fly, Musca domestica - Jeffrey G. Scott; Oshneil S. Baker; Anastacia E. Dressel; Rachel H. Norris; Edwin R. Burgess (Pesticide Biochemistry and Physiology, 2024)

Response surface methodology optimization of characteristics of biodiesel powered diesel engine and its effective integration to autonomous microgrid - Ramesh Kasimani; R. Sakthivel; Dhinesh Balasubramanian; JS Femilda Josephin; Arunachalam Chinnathambi; Edwin Geo Varuvel (Process Safety and Environmental Protection, 2024)

Synthetic phantoms enable calibration between abattoir based dual energy X-ray absorptiometers used for prediction of lamb carcass composition - Stephen Louis Connaughton; Andrew Williams; Fiona Anderson; Khama R. Kelman; Graham Edwin Gardner (Meat Science, 2024)

A new biphenyl from the stem bark of Garcinia macrantha A.C.Sm - Rifaldi; Edwin R. Sukandar; Arif Fadlan; Sri Fatmawati; Adi S. Purnomo; Johanis Wairata; Taslim Ersam (Natural Product Research, 2024)

An improved dung beetle optimization with recurrent convolutional neural networks for efficient detection and classification of undersea water object images - J. Jeno Jasmine; S. Edwin Raja; R. Muniraj; T. Jarin (Earth Science Informatics, 2024)

Elevated mercury exposure in bird communities inhabiting Artisanal and Small-Scale Gold Mining landscapes of the southeastern Peruvian Amazon - Jessica N. Pisconte; Claudia M. Vega; Christopher J. Sayers; C. Steven Sevillano-Ríos; Martin Pillaca; Edwin Quispe; Vania Tejeda; Cesar Ascorra; Miles R. Silman; Luis E. Fernandez (Ecotoxicology, 2024)

Publisher Correction to: In temperate Europe, fire is already here: The case of The Netherlands - Cathelijne R. Stoof; Edwin Kok; Adrián Cardil Forradellas; Margreet J. E. van Marle (Ambio, 2024)

Quantification of hardware effects of an on-line Dual Energy X-ray Absorptiometry scanner when predicting lamb carcass composition - Stephen Louis Connaughton; Andrew Williams; Fiona Anderson; Khama R. Kelman; Jarno Peterse; Graham Edwin Gardner (Meat Science, 2024)

Cross resistance to brevetoxin-3 by kdr and super-kdr mutations in house flies - Daniel R. Swale; Jeffrey R. Bloomquist; Sarah E. McComic; Edwin R. Burgess (Pesticide Biochemistry and Physiology, 2024)

Heavy metals concentration in soils across the conterminous USA: Spatial prediction, model uncertainty, and influencing factors - Kabindra Adhikari; Marcelo Mancini; Zamir Libohova; Joshua Blackstock; Edwin Winzeler; Douglas R. Smith; Phillip R. Owens; Sérgio H.G. Silva; Nilton Curi (Science of The Total Environment, 2024)

Engine behavior analysis on a conventional diesel engine combustion mode powered by low viscous cedarwood oil/waste cooking oil biodiesel/diesel fuel mixture – An experimental study - Van Nhanh Nguyen; Dhinesh Balasubramanian; Amudhan Rajarajan; Inbanaathan Papla Venugopal; C. Dineshkumar; R. Ravikumar; Duc Trong Nguyen Le; Dao Nam Cao; JS Femilda Josephin; Arunachalam Chinnathambi; Arivalagan Pugazhendhi; Edwin Geo Varuvel (Process Safety and Environmental Protection, 2024)

In temperate Europe, fire is already here: The case of The Netherlands - Cathelijne R. Stoof; Edwin Kok; Adrián Cardil Forradellas; Margreet J. E. van Marle (Ambio, 2024)
Landscape fires are usually not associated with temperate Europe, yet not all temperate countries record statistics indicating that actual risks remain unknown. Here we introduce new wildfire statistics for The Netherlands, and summarize significant events and fatalities. The period 2017–2022 saw 611 wildfires and 405 ha burned per year, which Copernicus’ European Forest Fire Information System satellite data vastly underestimate. Fires burned more heathland than forest, were small (mean fire size 1.5 ha), were caused by people, and often burned simultaneously, in Spring and in Summer drought. Suppression, restoration and traffic delays cost 3 M€ year −1 . Dozens of significant events illustrate fire has never been away and has major societal impact amidst grave concerns for firefighter safety. Since 1833, 31 fatalities were reported. A legal framework is needed to ensure continuity of recordkeeping, as the core foundation of integrated fire management, to create a baseline for climate change, and to fulfill international reporting requirements.

The duration of lithium use and biological ageing: telomere length, frailty, metabolomic age and all-cause mortality - Julian Mutz; Win Lee Edwin Wong; Timothy R. Powell; Allan H. Young; Gavin S. Dawe; Cathryn M. Lewis (GeroScience, 2024)
Lithium is an established first-line treatment for bipolar disorder. Beyond its therapeutic effect as a mood stabiliser, lithium exhibits potential anti-ageing effects. This study aimed to examine the relationship between the duration of lithium use, biological ageing and mortality. The UK Biobank is an observational study of middle-aged and older adults. We tested associations between the duration of lithium use (number of prescriptions, total duration of use and duration of the first prescription period) and telomere length, frailty, metabolomic age (MileAge) delta, pulse rate and all-cause mortality. Five hundred ninety-one individuals (mean age = 57.49 years; 55% females) had been prescribed lithium. There was no evidence that the number of prescriptions ( β = − 0.022, 95% CI − 0.081 to 0.037, p = 0.47), the total duration of use ( β = − 0.005, 95% CI − 0.023 to 0.013, p = 0.57) or the duration of the first prescription period ( β = − 0.018, 95% CI − 0.051 to 0.015, p = 0.29) correlated with telomere length. There was also no evidence that the duration of lithium use correlated with frailty or MileAge delta. However, a higher prescription count and a longer duration of use was associated with a lower pulse rate. The duration of lithium use did not predict all-cause mortality. We observed no evidence of associations between the duration of lithium use and biological ageing markers, including telomere length. Our findings suggest that the potential anti-ageing effects of lithium do not differ by the duration of use.

Microplastics on sandy beaches of Chiapas, Mexico - Khirbet López-Velázquez; Kevin G. Duque-Olivera; David A. Santiago-Gordillo; Edwin R. Hoil-Canul; Jorge L. Guzmán-Mar; Minerva Villanueva-Rodríguez; José G. Ronderos-Lara; Cesar Castillo-Quevedo; José L. Cabellos-Quiroz (Regional Studies in Marine Science, 2024)

Dose addition in mixtures of compounds with dissimilar endocrine modes of action in in vitro receptor activation assays and the zebrafish sexual development test - Toine FH. Bovee; Harm J. Heusinkveld; Sophie Dodd; Ad Peijnenburg; Deborah Rijkers; Marco Blokland; R Corinne Sprong; Amélie Crépet; Antsje Nolles; Edwin P. Zwart; Eric R. Gremmer; Leo TM van der Ven (Food and Chemical Toxicology, 2024)

Net effects explains the benefits to children from maternal fish consumption despite methylmercury in fish - Philip Spiller; Edwin van Wijngaarden; Heather R. Adams; J.J. Strain; Emeir M. McSorley; Maria S. Mulhern; Marie C. Conway; Allison J. Yeates; Clark Carrington; P. Michael Bolger; Kara M. Morgan; Caroline M. Taylor; et al. (NeuroToxicology, 2023)

History and Prospects for the Sustainability and Circularity of the Windowpane Oyster Placuna placenta Fishery in the Philippines - Jessica M. Rustia; Judith P. Antonino; Ravelina R. Velasco; Marcelo A. Lima; Edwin A. Yates; David G. Fernig (Fishes, 2023)
The windowpane oyster Placuna placenta lives in brackish coastal waters and has long been economically important to the Philippines because of its durable and translucent shell, which is used as a glass substitute and material for making windowpanes and handicrafts. There has been considerable degradation of the P. placenta fishery over the past decades. Moreover, there are waste and under-exploited by-products, such as the meat, which though nutritious and edible, currently has a very low value; its use is confined to dishes consumed by families in the fishing community. Historically, there have been instances of excellent practice in terms of regulating the P. placenta fishery, while in recent times, there have been local initiatives to restore this and to develop high-value food products from the meat. These initiatives have, however, never been followed through at a provincial or national level. Research on other molluscs and marine organisms highlights that these contain high-value pharmaceutical products, an unexplored facet of P. placenta. This review compiles evidence to establish the groundwork for an essential and comprehensive multidisciplinary research programme centred around the P. placenta, which would ensure a high value for all parts of the oyster, including those currently discarded. By fostering a sustainable and circular economy within this fishery sector and its associated industry, its economic value would be amplified. This is particularly important for oyster harvesters in the Philippines, who often find themselves on the economic ladder’s lower rungs. By integrating the principles of a circular economy, this initiative would not only aim to uplift the economic prospects of these harvesters, but in doing so would drive the restoration of P. placenta to its former range.

Fish and benthic communities in an offshore and well-managed coral reef after bleaching disturbance in the Philippines - Timothy Joseph R. Quimpo; Jeremiah Noelle Requilme; Elizabeth Gomez; Sherry Lyn Sayco; Edwin E. Dumalagan; Fernando P. Siringan; Cecilia Conaco; Patrick C. Cabaitan (Marine Biology, 2023)

Analysis of the impact of deploying thermal protective immersion suits on evacuation time for passenger ships operating in polar waters - Hooshyar Azizpour; Edwin R. Galea; Steven Deere; Sveinung Erland; Bjørn-Morten Batalden; Helle Oltedal (Ocean Engineering, 2023)

New records of Ornithodoros turicata (Ixodida: Argasidae) in rural and urban sites in the Mexican states of Aguascalientes and Zacatecas indicate the potential for tick-borne relapsing fever - Edwin Vázquez-Guerrero; José Luis González-Quiroz; María Lilia Domínguez-López; Alexander R. Kneubehl; Aparna Krishnavajhala; Michael W. Curtis; Alejandro Ponce-Mendoza; Paulina Estrada-de los Santos; Job E. Lopez; J. Antonio Ibarra (Experimental and Applied Acarology, 2023)

Defining the toxicological profile of 4-hydroxyphenylpyruvate dioxygenase-directed herbicides to Aedes aegypti and Amblyomma americanum - Sarah E. McComic; Stephen O. Duke; Edwin R. Burgess; Daniel R. Swale (Pesticide Biochemistry and Physiology, 2023)

A note on graphite hydrogenation as a source of abiotic methane on rocky planets: A case study for Mercury - Camille R. Butkus; Alexandra O. Warren; Edwin S. Kite; Santiago Torres; Smadar Naoz; Jennifer B. Glass (Icarus, 2023)

Amber and the Cretaceous Resinous Interval - Xavier Delclòs; Enrique Peñalver; Eduardo Barrón; David Peris; David A. Grimaldi; Michael Holz; Conrad C. Labandeira; Erin E. Saupe; Christopher R. Scotese; Mónica M. Solórzano-Kraemer; Sergio Álvarez-Parra; Antonio Arillo; et al. (Earth-Science Reviews, 2023)

Schomburginones A‒J, geranylated benzophenones from the leaves of Garcinia schomburgkiana and their cytotoxic and anti-inflammatory activities - Edwin R. Sukandar; Sutin Kaennakam; Sutthida Wongsuwan; Jaruwan Chatwichien; Sucheewin Krobthong; Yodying Yingchutrakul; Thanisorn Mahatnirunkul; Fadjar Mulya; Vudhichai Parasuk; David J. Harding; Preeyaporn Poldorn; Thanyada Rungrotmongkol; et al. (Phytochemistry, 2023)

Transferability and reproducibility of exposed air-liquid interface co-culture lung models - Hedwig M. Braakhuis; Eric R. Gremmer; Anne Bannuscher; Barbara Drasler; Sandeep Keshavan; Barbara Rothen-Rutishauser; Barbara Birk; Andreas Verlohner; Robert Landsiedel; Kirsty Meldrum; Shareen H. Doak; Martin J.D. Clift; et al. (NanoImpact, 2023)

Enhancing the performance of renewable biogas powered engine employing oxyhydrogen: Optimization with desirability and D-optimal design - Prabhakar Sharma; Dhinesh Balasubramanian; Chu Thanh Khai; Inbanaathan Papla Venugopal; Mansoor Alruqi; Femilda Josephin JS; Ankit Sonthalia; Edwin Geo Varuvel; Esmail Khalife; R. Ravikumar; Makatar Wae-Hayee (Fuel, 2023)

A farmer-friendly tool for estimation of weights of pigs kept by smallholder farmers in Uganda - Karen Marshall; Jane Poole; Edwin Oyieng; Emily Ouma; Donald R. Kugonza (Tropical Animal Health and Production, 2023)
Pig keeping is important to the livelihoods of many rural Ugandans. Pigs are typically sold based on live weight or a carcass weight derived from this; however this weight is commonly estimated due to the lack of access to scales. Here, we explore the development of a weigh band for more accurate weight determination and potentially increased farmer bargaining power on sale price. Pig weights and varied body measurements (heart girth, height, and length) were collected on 764 pigs of different ages, sex, and breed types, from 157 smallholder pig keeping households in Central and Western Uganda. Mixed-effects linear regression analyses, with household as a random effect and the varied body measurements as a fixed effect, were performed to determine the best single predictor for cube root of weight (transformation of weight for normality), for 749 pigs ranging between 0 and 125 kg. The most predictive single body measurement was heart girth, where weight in kg = (0.4011 + heart girth in cm × 0.0381) 3 . This model was found to be most suitable for pigs between 5 and 110 kg, notably more accurate than farmers’ estimates, but still with somewhat broad confidence intervals (for example, ±11.5 kg for pigs with a predicted weight of 51.3 kg). We intend to pilot test a weigh band based on this model before deciding on whether it is suitable for wider scaling.

Process Optimization of Lipid Extraction from Microalgae Aphanothece halophytica in Wet and Dry Conditions - L. R. Monisha Miriam; Ajith J. Kings; R. Edwin Raj; K. Prakash Shyam; M. Adhi Viswanathan (BioEnergy Research, 2023)

Garcowacinols A-J, cytotoxic polyprenylated benzoylphloroglucinol derivatives from the twigs of Garcinia cowa - Sutin Kaennakam; Edwin R. Sukandar; Pattama Phasuthan; Jantana Yahuafai; Prayumat Onsrisawat; Fadjar Mulya; Vudhichai Parasuk; Preecha Phuwapraisirisan; Santi Tip-pyang (Phytochemistry, 2023)

Genomic insights of Leclercia adecarboxylata strains linked to an outbreak in public hospitals in Mexico - Edwin Barrios-Villa; Brenda Pacheco-Flores; Patricia Lozano-Zaraín; Rodolfo Del Campo-Ortega; Ivan de Jesús Ascencio-Montiel; Margot González-León; Margarita Camorlinga-Ponce; Francisco Javier Gaytán Cervantes; Carolina González Torres; Emmanuel Aguilar; Joaquín González Ibarra; Francisco Javier Torres López; et al. (Genes & Genomics, 2023)

Selection for, and characterization of, fluralaner resistance in the house fly, Musca domestica - Rachel H. Norris; Oshneil S. Baker; Edwin R. Burgess; Aaron Tarone; Alec Gerry; Rebecca T. Trout Fryxell; Nancy C. Hinkle; Cassandra Olds; David Boxler; Kenneth L. Wise; Erika T. Machtinger; Jeffrey G. Scott (Pesticide Biochemistry and Physiology, 2023)

Monitoring and modeling dispersal of a submerged nearshore berm at the mouth of the Columbia River, USA - Andrew W. Stevens; Hans R. Moritz; Edwin P.L. Elias; Guy R. Gelfenbaum; Peter R. Ruggiero; Stuart G. Pearson; James M. McMillan; George M. Kaminsky (Coastal Engineering, 2023)

Can spatial food web subsidies associated with river hydrology and lateral connectivity be detected using stable isotopes? - Kirk O. Winemiller; Marcelo C. Andrade; Caroline C. Arantes; Thethela Bokhutlo; Luke M. Bower; Eduardo R. Cunha; Friedrich W. Keppeler; Edwin O. López-Delgado; Yasmin Quintana; David E. Saenz; Kevin B. Mayes; Clint R. Robertson (Food Webs, 2023)

Fuel use in small-scale fishing vessels along the southeast coast of India: a comparative study to ascertain possible reasons and potential recommendations for effective management - Kumarakannan Asokan; Paras Nath Jha; Leela Edwin; Manoj Kumar B; Amrutha R. Krishnan; Mathew Sebastian (Environmental Monitoring and Assessment, 2023)

Towards effective reforestation: growth and commercial value of four commonly planted tropical timber species on infertile soils in Panama - Katherine Sinacore; Edwin H. García; Theodore Howard; Michiel van Breugel; Omar R. Lopez; Alex J. Finkral; Jefferson S. Hall (New Forests, 2023)
Finding suitable tree species that not only grow well on nutrient poor soils but are also safe financial investments is one of the major obstacles to successful reforestation efforts in the tropics. Our study compared the financial viability and growth of valuable timber species in monocultures and mixtures on infertile soils. Our work shows the extraordinary growth in volume and value of Dalbergia retusa and Terminalia amazonia while underscoring the poor financial viability of Tectona grandis and Pachira quinata , all commonly planted timber species in Panama and much of Central and South America. Using Bayesian statistics, our predictions show that T. amazonia monocultures could reach nearly 200 m 3 ha −1 of merchantable volume after 30 years compared to the ~ 40 m 3 ha −1 that T. grandis could accumulate in the same time frame. While D. retusa monocultures did not have the highest predicted merchantable volumes of all the species, it did have the highest predicted net present value (NPV), with a predicted mean NPV of > US$97,000 ha −1 , quadrupling the species with the next highest monoculture’s NPV, T. amazonia monocultures (~ US$20,000 ha −1 ). Our work emphasizes that reforestation can be financially viable on low nutrient soils, even in the absence of fertilization or other silvicultural manipulations, if species selection and site are carefully considered and matched.

Impact of Covishield Vaccination in Terms of SARS CoV-2 Neutralizing Antibody Expression - Rhema Elizabeth Thomas; Ajaikumar Sukumaran; Arun Krishnan R; Thushara Thomas; Biby T Edwin; P R Haritha; Bilha M Varghese; Jofy K Paul; Satheesh Kumar C S; D M Vasudevan (Indian Journal of Clinical Biochemistry, 2023)

A Hashing-Based Framework for Enhancing Cluster Delineation of High-Dimensional Single-Cell Profiles - Xiao Liu; Ting Zhang; Ziyang Tan; Antony R. Warden; Shanhe Li; Edwin Cheung; Xianting Ding (Phenomics, 2022)

Long-lasting effects of experimental flow intermittency on alpine stream macroinvertebrates (Val Roseg, Switzerland) - Annemieke M. Drost; Andre R. Siebers; Amael Paillex; Benjamin Misteli; Edwin T. H. M. Peeters; Christopher T. Robinson (Hydrobiologia, 2022)
Changing weather patterns and receding glaciers are predicted to increase flow intermittency in alpine streams. If aquatic macroinvertebrate communities largely comprise taxa adapted to perennial flows, an increase in flow intermittency substantially reduces biodiversity and affects functional processes. We conducted a before-after-control-impact field experiment to examine how macroinvertebrate communities in an alpine headwater stream responded to and recovered from a repeated experimental increase in flow intermittency. Flow in one channel was manipulated to simulate increased summer intermittency (June–September) over two consecutive years, whilst an adjacent channel served as a control. We monitored the density of benthic macroinvertebrates, periphyton and organic matter at approximately monthly intervals over three years during the snow-free period. Before manipulation, both channels had similar ecological properties. The flow manipulation reduced the overall macroinvertebrate density, and especially the proportional rheophile density, across both years. Recovery of the macroinvertebrate community following experimental flow intermittency took more than a year, and longer than our study period. This could be due to long aquatic life stages, dispersal limitation and biotic interactions. We conclude that climate-induced changes in alpine stream flow regimes can lead to a fundamental shift in macroinvertebrate assemblages through local extinctions, mostly of rheophilic species.

Characterizing malaria spatial distribution in the province of Palawan, Philippines - Nicole Faith D. Blanco; Arnold R. Salvacion; Ma. Catriona E. Devanadera; Edwin R. Abucay; Ricardo A. Sandalo (Spatial Information Research, 2022)

Marine Snow-Oil Interaction Affects n-Alkane Biodegradation in Sediment - Shokouh Rahsepar; Justine S. van Eenennaam; Jagoš R. Radović; Thomas B. P. Oldenburg; Huub H. M. Rijnaarts; Albertinka J. Murk; Edwin M. Foekema; Alette A. M. Langenhoff (Water, Air, & Soil Pollution, 2022)
During the Deepwater Horizon (DwH) oil spill, an excessive production of marine snow was observed, and it was estimated that as much as 14% of the oil was transferred to the ocean floor by MOSSFA (Marine Oil Snow Sedimentation and Flocculent Accumulation). MOSSFA is an important pathway of transferring oil to the ocean floor. We performed experiments at laboratory scale in 15 aquaria, representing 5 exposures of marine snow with or without oil, only oil, and controls with only clay or sediment. We developed a method to produce artificial marine snow, which resembles the natural marine snow. Results showed 40% less biodegradation of alkanes in “marine snow with oil” compared to “only oil.” Most probably, this is due to preferred biodegradation of marine snow organics comparing to oil alkanes. Biodegradation of marine snow reduces the dissolved oxygen concentration, which might result in anaerobic conditions in the sediment layer. This finding can be projected to a potential ocean floor effect.

Impact of Land Use Conversion on Carbon Stocks and Selected Peat Physico-chemical Properties in the Leyte Sab-a Basin Peatland, Philippines - Syrus Cesar P. Decena; Sarah Villacorta-Parilla; Arwin O. Arribado; Dionesio R. Macasait; Michael S. Arguelles; Shella S. Salamia; Edwin S. Relevo (Wetlands, 2022)

Circulating levels of calprotectin, a signature of neutrophil activation in prediction of severe respiratory failure in COVID-19 patients: a multicenter, prospective study (CalCov study) - Luis García de Guadiana-Romualdo; Carlos Rodríguez Rojas; Daniel Morell-García; David Andaluz-Ojeda; María Dolores Rodríguez Mulero; Enrique Rodríguez-Borja; Antonieta Ballesteros-Vizoso; María Dolores Calvo; Lourdes Albert-Botella; Adela Pozo Giráldez; Isabel Llompart-Alabern; Cristina Bolado Jiménez; et al. (Inflammation Research, 2022)

Examining the etiology of early-onset breast cancer in the Canadian Partnership for Tomorrow’s Health (CanPath) - Joy Pader; Robert B. Basmadjian; Dylan E. O’Sullivan; Nicole E. Mealey; Yibing Ruan; Christine Friedenreich; Rachel Murphy; Edwin Wang; May Lynn Quan; Darren R. Brenner (Cancer Causes & Control, 2021)

Species and functional diversity of macrofungi from protected areas in mountain forest ecosystems of Southern Luzon, Philippines - Jason A. Parlucha; Janine Kaysee R. Soriano; Milbrenne D. Yabes; Nelson M. Pampolina; Edwin R. Tadiosa (Tropical Ecology, 2021)

Detection of porcine circovirus type 2 (PCV2) in the Philippines and the complexity of PCV2-associated disease diagnosis - Agnes dela Cruz; Chiara Palmieri; Rachel Azul; Christina Legaspi; Suzan Lola; Tamsin S. Barnes; Christopher R. Parke; Conny Turni; John I. Alawneh; Augusto S. Baluyut; Voltaire G. Basinang; Jose E. David; et al. (Tropical Animal Health and Production, 2021)

Pathogenic variants in CDH11 impair cell adhesion and cause Teebi hypertelorism syndrome - Dong Li; Michael E. March; Paola Fortugno; Liza L. Cox; Leticia S. Matsuoka; Rosanna Monetta; Christoph Seiler; Louise C. Pyle; Emma C. Bedoukian; María José Sánchez-Soler; Oana Caluseriu; Katheryn Grand; et al. (Human Genetics, 2021)

Experimental investigation of discarded additive material combination and composition to appropriate thermal insulating properties of the composite cement mortar - Y. Balto; R. Edwin Raj; J. Anne Chandra; S. C. Vettivel (European Journal of Environmental and Civil Engineering, 2021)

Reversible thrombocytopenia during hibernation originates from storage and release of platelets in liver sinusoids - Edwin L. de Vrij; Hjalmar R. Bouma; Maaike Goris; Ulrike Weerman; Anne P. de Groot; Jeroen Kuipers; Ben N. G. Giepmans; Robert H. Henning (Journal of Comparative Physiology B, 2021)
Immobility is a risk factor for thrombosis due to low blood flow, which may result in activation of the coagulation system, recruitment of platelets and clot formation. Nevertheless, hibernating animals—who endure lengthy periods of immobility—do not show signs of thrombosis throughout or after hibernation. One of the adaptations of hemostasis in hibernators consists of a rapidly reversible reduction of the number of circulating platelets during torpor, i.e., the hibernation phase with reduction of metabolic rate, low blood flow and immobility. It is unknown whether these platelet dynamics in hibernating hamsters originate from storage and release, as suggested for ground squirrel, or from breakdown and de novo synthesis. A reduction in detaching forces due to low blood flow can induce reversible adhesion of platelets to the vessel wall, which is called margination. Here, we hypothesized that storage-and-release by margination to the vessel wall induces reversible thrombocytopenia in torpor. Therefore, we transfused labeled platelets in hibernating Syrian hamster ( Mesocricetus auratus ) and platelets were analyzed using flow cytometry and electron microscopy. The half-life of labeled platelets was extended from 20 to 30 h in hibernating animals compared to non-hibernating control hamsters. More than 90% of labeled platelets were cleared from the circulation during torpor, followed by emergence during arousal which supports storage-and-release to govern thrombocytopenia in torpor. Furthermore, the low number of immature platelets, plasma level of interleukin-1α and normal numbers of megakaryocytes in bone marrow make platelet synthesis or megakaryocyte rupture via interleukin-1α unlikely to account for the recovery of platelet counts upon arousal. Finally, using large-scale electron microscopy we revealed platelets to accumulate in liver sinusoids, but not in spleen or lung, during torpor. These results thus demonstrate that platelet dynamics in hibernation are caused by storage and release of platelets, most likely by margination to the vessel wall in liver sinusoids. Translating the molecular mechanisms that govern platelet retention in the liver, may be of major relevance for hemostatic management in (accidental) hypothermia and for the development of novel anti-thrombotic strategies.

Late Pleistocene biota from Pubenza, Colombia; turtles, mammals, birds, invertebrates and plant remains - AndrÉs Alfonso‐Rojas; Laura M. Herrera‐Gutierrez; Catalina SuÁRez; MartÍN R. Ciancio; Jonathan S. Pelegrin; Edwin‐Alberto Cadena (Journal of Quaternary Science, 2021)
Pubenza is a remarkable palaeontological site of Colombia, and a place that could hold some of the potentially oldest evidence of humans in northern South America. Previous palaeontological research at this site has mainly focused on the megafauna. Here we describe and establish the systematic palaeontology for the small fauna that inhabited this ancient lacustrine ecosystem, including the first report of birds, tortoises and vipers for the Late Pleistocene in Colombia. Furthermore, exceptionally well preserved fossilised wasp nests are morphologically and elementally characterised, which is the first report of an ichnofossil of this kind in northern South America. In addition, new material of kinosternid turtles, armadillos and rodents is also described. Our results reveal that the Bogotá River Basin, where Pubenza is located, was a rich ecosystem during the Late Pleistocene and a region of great interest for future articulated palaeontological and archaeological studies.

Beyond species counts for assessing, valuing, and conserving biodiversity: response to Wallach et al. 2019 - Ninon F. V. Meyer; Niko Balkenhol; Trishna Dutta; Maarten Hofman; Jean‐Yves Meyer; Euan G. Ritchie; Charlotte Alley; Chad Beranek; Cassandra K. Bugir; Alex Callen; Simon Clulow; Michael V. Cove; et al. (Conservation Biology, 2021)
Article impact statement : Combining native and non‐native species to evaluate biodiversity is overly simplistic and may undermine the conservation of ecosystems.

Carcass Additions Influence Food Webs Through Bottom-Up and Direct Consumption Pathways Along a Fish Species Assemblage Gradient - Matthew J. Kaylor; Seth M. White; Edwin R. Sedell; Ashley M. Sanders; Dana R. Warren (Ecosystems, 2021)

Mutagenicity of acrylamide and glycidamide in human TP53 knock-in (Hupki) mouse embryo fibroblasts - Lisa Hölzl-Armstrong; Jill E. Kucab; Sarah Moody; Edwin P. Zwart; Lucie Loutkotová; Veronica Duffy; Mirjam Luijten; Gonçalo Gamboa da Costa; Michael R. Stratton; David H. Phillips; Volker M. Arlt (Archives of Toxicology, 2020)
Acrylamide is a suspected human carcinogen formed during high-temperature cooking of starch-rich foods. It is metabolised by cytochrome P450 2E1 to its reactive metabolite glycidamide, which forms pre-mutagenic DNA adducts. Using the human TP53 knock-in (Hupki) mouse embryo fibroblasts (HUFs) immortalisation assay (HIMA), acrylamide- and glycidamide-induced mutagenesis was studied in the tumour suppressor gene TP53 . Selected immortalised HUF clones were also subjected to next-generation sequencing to determine mutations across the whole genome. The TP53 -mutant frequency after glycidamide exposure (1.1 mM for 24 h, n = 198) was 9% compared with 0% in cultures treated with acrylamide [1.5 ( n = 24) or 3 mM ( n = 6) for 48 h] and untreated vehicle (water) controls ( n = 36). Most glycidamide-induced mutations occurred at adenines with A > T/T > A and A > G/T > C mutations being the most common types. Mutations induced by glycidamide occurred at specific TP53 codons that have also been found to be mutated in human tumours (i.e., breast, ovary, colorectal, and lung) previously associated with acrylamide exposure. The spectrum of TP53 mutations was further reflected by the mutations detected by whole-genome sequencing (WGS) and a distinct WGS mutational signature was found in HUF clones treated with glycidamide that was again characterised by A > G/T > C and A > T/T > A mutations. The WGS mutational signature showed similarities with COSMIC mutational signatures SBS3 and 25 previously found in human tumours (e.g., breast and ovary), while the adenine component was similar to COSMIC SBS4 found mostly in smokers’ lung cancer. In contrast, in acrylamide-treated HUF clones, only culture-related background WGS mutational signatures were observed. In summary, the results of the present study suggest that glycidamide may be involved in the development of breast, ovarian, and lung cancer.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Hippocampal viscoelasticity and episodic memory performance in healthy older adults examined with magnetic resonance elastography - Lucy V. Hiscox; Curtis L. Johnson; Matthew D. J. McGarry; Hillary Schwarb; Edwin J. R. van Beek; Neil Roberts; John M. Starr (Brain Imaging and Behavior, 2020)

The unaddressed threat of invasive animals in U.S. National Parks - Ashley A. Dayer; Kent H. Redford; Karl J. Campbell; Christopher R. Dickman; Rebecca S. Epanchin-Niell; Edwin D. Grosholz; David E. Hallac; Elaine F. Leslie; Leslie A. Richardson; Mark W. Schwartz (Biological Invasions, 2020)

Multidisciplinary Observing in the World Ocean’s Oxygen Minimum Zone Regions: From Climate to Fish — The VOICE Initiative - Véronique Garçon; Johannes Karstensen; Artur Palacz; Maciej Telszewski; Tony Aparco Lara; Denise Breitburg; Francisco Chavez; Paulo Coelho; Marcela Cornejo-D’Ottone; Carmen Santos; Björn Fiedler; Natalya D. Gallo; et al. (Frontiers in Marine Science, 2019)

Enabling self-management of pollen allergies: a pre-season questionnaire evaluating the perceived benefit of providing local pollen information - Danielle E. Medek; Marko Simunovic; Bircan Erbas; Constance H. Katelaris; Edwin R. Lampugnani; Alfredo Huete; Paul J. Beggs; Janet M. Davies (Aerobiologia, 2019)

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Induced Plant Defenses Against Herbivory in Cultivated and Wild Tomato - Sulav Paudel; Po-An Lin; Majid R. Foolad; Jared G. Ali; Edwin G. Rajotte; Gary W. Felton (Journal of Chemical Ecology, 2019)

Scaling issues of neutral theory reveal violations of ecological equivalence for dominant Amazonian tree species - Edwin Pos; Juan Ernesto Guevara; Jean‐François Molino; Daniel Sabatier; Olaf S. Bánki; Nigel C.A. Pitman; Hugo F. Mogollón; Roosevelt García‐Villacorta; David Neill; Oliver L. Phillips; Carlos Cerón; Marcos Ríos Paredes; et al. (Ecology Letters, 2019)
Neutral models are often used as null models, testing the relative importance of niche versus neutral processes in shaping diversity. Most versions, however, focus only on regional scale predictions and neglect local level contributions. Recently, a new formulation of spatial neutral theory was published showing an incompatibility between regional and local scale fits where especially the number of rare species was dramatically under‐predicted. Using a forward in time semi‐spatially explicit neutral model and a unique large‐scale Amazonian tree inventory data set, we show that neutral theory not only underestimates the number of rare species but also fails in predicting the excessive dominance of species on both regional and local levels. We show that although there are clear relationships between species composition, spatial and environmental distances, there is also a clear differentiation between species able to attain dominance with and without restriction to specific habitats. We conclude therefore that the apparent dominance of these species is real, and that their excessive abundance can be attributed to fitness differences in different ways, a clear violation of the ecological equivalence assumption of neutral theory.

Cold treatment prompts embryogenic callus and cytodifferentiation in the anthers of tea (Camellia sp.) genotypes - CH. Naga Pavan Kumar; E. Edwin Raj; P. Mohan Kumar; R. Raj Kumar; K. N. Chandrashekara (Plant Physiology Reports, 2019)

NOx emission reduction using permanent/electromagnet-based fuel reforming system in a compression ignition engine fueled with pine oil - S. Thiyagarajan; V. Edwin Geo; B. Ashok; K. Nanthagopal; R. Vallinayagam; C. G. Saravanan; P. Kumaran (Clean Technologies and Environmental Policy, 2019)

Spatial variability in reef‐fish assemblages in shallow and upper mesophotic coral ecosystems in the Philippines - Timothy J. R. Quimpo; Patrick C. Cabaitan; Ronald D. D. Olavides; Edwin E. Dumalagan Jr.; Jeffrey Munar; Fernando P. Siringan (Journal of Fish Biology, 2019)
The variability in reef‐fish species assemblages was examined at three geographic locations in the Philippines (Apo, Abra and Patn), each showing varying levels of disturbances (low to high) at two depths, shallow‐water reef (SWR; 8–20 m) and the upper mesophotic coral ecosystem (MCE; 30–35 m). Fish species assemblages varied among locations and between depths. Differences in fish assemblages among locations corresponded to the variability in benthic assemblages and levels of disturbances, wherein locations with higher coral cover and less disturbances had the highest fish species richness, abundance and biomass. Variation in fish assemblages between depths was also associated with changes in benthic assemblages and possibly inaccessibility to local fishing techniques. Fish species richness decreased with depth in all locations, but biomass increased only in the MCEs of Apo and Abra, which is a similar pattern exhibited in many MCEs. Our results suggest that despite location differences, depth had a relatively consistent influence on fish species assemblages, particularly in locations exposed to low and intermediate disturbance. Under high disturbance, MCEs exhibit similar vulnerability to SWRs.

Head skeleton malformations in zebrafish (Danio rerio) to assess adverse effects of mixtures of compounds - Yvonne C. M. Staal; Jeroen Meijer; Remco J. C. van der Kris; Annamaria C. de Bruijn; Anke Y. Boersma; Eric R. Gremmer; Edwin P. Zwart; Piet K. Beekhof; Wout Slob; Leo T. M. van der Ven (Archives of Toxicology, 2018)

Higher habitual dietary caffeine consumption is related to lower experimental pain sensitivity in a community-based sample - Demario S. Overstreet; Terence M. Penn; Sarah T. Cable; Edwin N. Aroke; Burel R. Goodin (Psychopharmacology, 2018)

Role of fuel additives on reduction of NOX emission from a diesel engine powered by camphor oil biofuel - Thiyagarajan Subramanian; Edwin Geo Varuvel; Saravanan Ganapathy; S. Vedharaj; R. Vallinayagam (Environmental Science and Pollution Research, 2018)

Development of endothermy in birds: patterns and mechanisms - Edwin R. Price; Edward M. Dzialowski (Journal of Comparative Physiology B, 2018)

The influence of sex and diet on the characteristics of hibernation in Syrian hamsters - Marie Trefna; Maaike Goris; Cynthia M. C. Thissen; Vera A. Reitsema; Jojanneke J. Bruintjes; Edwin L. de Vrij; Hjalmar R. Bouma; Ate S. Boerema; Robert H. Henning (Journal of Comparative Physiology B, 2017)

19F labelled glycosaminoglycan probes for solution NMR and non-linear (CARS) microscopy - Marcelo A. Lima; Renan P. Cavalheiro; Gustavo M.Viana; Maria C.Z. Meneghetti; Timothy R. Rudd; Mark A. Skidmore; Andrew K. Powell; Edwin A. Yates (Glycoconjugate Journal, 2017)

Whole grain in manufactured foods: Current use, challenges and the way forward - Christelle Schaffer-Lequart; Undine Lehmann; Alastair B. Ross; Olivier Roger; Alison L. Eldridge; Edwin Ananta; Marie-France Bietry; Luis R. King; Alice V. Moroni; Sathaporn Srichuwong; Anne-Sophie Wavreille; Robert Redgwell; et al. (Critical Reviews in Food Science and Nutrition, 2017)

Herbivorous fishes Siganus rivulatus (Siganidae) and Zebrasoma desjardinii (Acanthuridae) feed on Ctenophora and Scyphozoa in the Red Sea - Arthur R. Bos; Edwin Cruz-Rivera; Ashraf M. Sanad (Marine Biodiversity, 2017)

Sublethal effects of imidacloprid exposure on Spalangia endius, a pupal parasitoid of filth flies - Edwin R. Burgess; Aspen Kremer; Sherine F. Elsawa; B. H. King (BioControl, 2017)

Fringing trees may provide a refuge from prolonged drying for urban wetland invertebrates - Scott R. Strachan; Edwin T. Chester; Belinda J. Robson (Urban Ecosystems, 2016)

Utilizing an Ingestible Biosensor to Assess Real-Time Medication Adherence - Peter R. Chai; Jose Castillo-Mancilla; Eric Buffkin; Chad Darling; Rochelle K. Rosen; Keith J. Horvath; Edwin D. Boudreaux; Gregory K. Robbins; Patricia L. Hibberd; Edward W. Boyer (Journal of Medical Toxicology, 2015)

Oil in the Gulf of Mexico after the capping of the BP/Deepwater Horizon Mississippi Canyon (MC-252) well - Steve R. Kolian; Scott A. Porter; Paul W. Sammarco; Detlef Birkholz; Edwin W. Cake; Wilma A. Subra (Environmental Science and Pollution Research, 2015)

Sensory, Biochemical, and Microbial Qualities of Canned Farmed Cobia Processed with Indian Spice Masala Mix - R. Jeya Shakila; B. Edwin Raj; N. Felix (Journal of Aquatic Food Product Technology, 2015)

Aquaculture as a vector for marine invasions in California - Edwin D. Grosholz; R. Eliot Crafton; Rachel E. Fontana; Jae R. Pasari; Susan L. Williams; Chela J. Zabin (Biological Invasions, 2015)

Real-Time Mobile Detection of Drug Use with Wearable Biosensors: A Pilot Study - Stephanie Carreiro; David Smelson; Megan Ranney; Keith J. Horvath; R. W. Picard; Edwin D. Boudreaux; Rashelle Hayes; Edward W. Boyer (Journal of Medical Toxicology, 2015)

Systemic oxygenation weakens the hypoxia and hypoxia inducible factor 1α-dependent and extracellular adenosine-mediated tumor protection - Stephen M. Hatfield; Jorgen Kjaergaard; Dmitriy Lukashev; Bryan Belikoff; Taylor H. Schreiber; Shalini Sethumadhavan; Robert Abbott; Phaethon Philbrook; Molly Thayer; Dai Shujia; Scott Rodig; Jeffrey L. Kutok; et al. (Journal of Molecular Medicine, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

A simulation model for nitrogen cycling in natural rooted papyrus wetlands in East Africa - Edwin M. A. Hes; R. Niu; Anne A. van Dam (Wetlands Ecology and Management, 2014)

Human and Non-Human Primate Intestinal FcRn Expression and Immunoglobulin G Transcytosis - Pamela J. Hornby; Philip R. Cooper; Connie Kliwinski; Edwin Ragwan; John R. Mabus; Benjamin Harman; Suzanne Thompson; Amanda L. Kauffman; Zhengyin Yan; Susan H. Tam; Haimanti Dorai; Gordon D. Powers; et al. (Pharmaceutical Research, 2014)

Detection of ammonia-oxidizing Bacteria and Archaea within coral reef cyanobacterial mats - Dmitri Sobolev; Matthew R. Boyett; Edwin Cruz-Rivera (Journal of Oceanography, 2013)

A role for histamine in cardiovascular regulation in late stage embryos of the red-footed tortoise, Chelonoidis carbonaria Spix, 1824 - Dane A. Crossley; Marina R. Sartori; Augusto S. Abe; Edwin W. Taylor (Journal of Comparative Physiology B, 2013)

Probabilistic estimates of future changes in California temperature and precipitation using statistical and dynamical downscaling - David W. Pierce; Tapash Das; Daniel R. Cayan; Edwin P. Maurer; Norman L. Miller; Yan Bao; M. Kanamitsu; Kei Yoshimura; Mark A. Snyder; Lisa C. Sloan; Guido Franco; Mary Tyree (Climate Dynamics, 2013)

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD - Nadia N. Hansel; Ingo Ruczinski; Nicholas Rafaels; Don D. Sin; Denise Daley; Alla Malinina; Lili Huang; Andrew Sandford; Tanda Murray; Yoonhee Kim; Candelaria Vergara; Susan R. Heckbert; et al. (Human Genetics, 2013)

Genome-wide association mapping of loci for antipsychotic-induced extrapyramidal symptoms in mice - James J. Crowley; Yunjung Kim; Jin Peng Szatkiewicz; Amanda L. Pratt; Corey R. Quackenbush; Daniel E. Adkins; Edwin van den Oord; Molly A. Bogue; Hyuna Yang; Wei Wang; David W. Threadgill; Fernando Pardo-Manuel de Villena; et al. (Mammalian Genome, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Effect of ageing on the murine venous circulation - Bianca Hemmeryckx; Jan Emmerechts; Edwin G. Bovill; Marc F. Hoylaerts; H. R. Lijnen (Histochemistry and Cell Biology, 2012)

Transgenic Stra8-EYFP pigs: a model for developing male germ cell technologies - Jeffrey R. Sommer; Lauren R. Jackson; Sean G. Simpson; Edwin B. Collins; Jorge A. Piedrahita; Robert M. Petters (Transgenic Research, 2012)

Impacts of atmospheric nitrogen deposition: responses of multiple plant and soil parameters across contrasting ecosystems in long‐term field experiments - Gareth K. Phoenix; Bridget A. Emmett; Andrea J. Britton; Simon J. M. Caporn; Nancy B. Dise; Rachel Helliwell; Laurence Jones; Jonathan R. Leake; Ian D. Leith; Lucy J. Sheppard; Alwyn Sowerby; Michael G. Pilkington; et al. (Global Change Biology, 2012)
Atmospheric nitrogen ( N ) deposition is a global and increasing threat to biodiversity and ecosystem function. Much of our current understanding of N deposition impacts comes from field manipulation studies, although interpretation may need caution where simulations of N deposition (in terms of dose, application rate and N form) have limited realism. Here, we review responses to simulated N deposition from the UKREATE network, a group of nine experimental sites across the UK in a diversity of heathland, grassland, bog and dune ecosystems which include studies with a high level of realism and where many are also the longest running globally on their ecosystem type. Clear responses were seen across the sites with the greatest sensitivity shown in cover and species richness of bryophytes and lichens. Productivity was also increased at sites where N was the limiting nutrient, while flowering also showed high sensitivity, with increases and declines seen in dominant shrub and forb species, respectively. Critically, these parameters were responsive to some of the lowest additional loadings of N (7.7–10 kg ha −1 yr −1 ) showing potential for impacts by deposition rates seen in even remote and ‘unpolluted’ regions of E urope. Other parameters were less sensitive, but nevertheless showed response to higher doses. These included increases in soil % N and ‘plant available’ KCl extractable N , N cycling rates and acid–base status. Furthermore, an analysis of accumulated dose that quantified response against the total N input over time suggested that N impacts can ‘build up’ within an ecosystem such that even relatively low N deposition rates can result in ecological responses if continued for long enough. Given the responses have important implications for ecosystem structure, function, and recovery from N loading, the clear evidence for impacts at relatively low N deposition rates across a wide range of habitats is of considerable concern.

The structure and functioning of the couplon in the mammalian cardiomyocyte - Parisa Asghari; David R. L. Scriven; Jeremy Hoskins; Nicola Fameli; Cornelis van Breemen; Edwin D. W. Moore (Protoplasma, 2012)

Optimization of cell-based assays to quantify the anti-inflammatory/allergic potential of test substances in 96-well format - C. V. Chandrasekaran; R. Edwin Jothie; Preeti Kapoor; Anumita Gupta; Amit Agarwal (Inflammopharmacology, 2011)

Flight muscle shape reliably predicts flight muscle mass of migratory songbirds: a new tool for field ornithologists - Ulf Bauchinger; Scott R. McWilliams; Harald Kolb; Vladimir M. Popenko; Edwin R. Price; Herbert Biebach (Journal of Ornithology, 2011)

Genome-wide analysis of copy number variants in age-related macular degeneration - Kacie J. Meyer; Lea K. Davis; Emily I. Schindler; John S. Beck; Danielle S. Rudd; A. Jason Grundstad; Todd E. Scheetz; Terry A. Braun; John H. Fingert; Wallace L. Alward; Young H. Kwon; James C. Folk; et al. (Human Genetics, 2011)

Carnitine palmitoyl transferase activity and whole muscle oxidation rates vary with fatty acid substrate in avian flight muscles - Edwin R. Price; James F. Staples; C. Louise Milligan; Christopher G. Guglielmo (Journal of Comparative Physiology B, 2010)

Quantitative Temporal Profiles of Penumbra and Infarction During Permanent Middle Cerebral Artery Occlusion in Rats - Lesley M. Foley; T. Kevin. Hitchens; Brent Barbe; Feng Zhang; Chien Ho; Gutti R. Rao; Edwin M. Nemoto (Translational Stroke Research, 2010)

Are deep‐sea demersal fish assemblages globally homogenous? Insights from seamounts - Malcolm R. Clark; Franziska Althaus; Alan Williams; Edwin Niklitschek; Gui M. Menezes; Nils‐Roar Hareide; Philip Sutton; Ciaran O’Donnell (Marine Ecology, 2010)
Deep‐sea fishes have been poorly sampled globally, and overall knowledge of demersal fish distributions and the drivers of community composition and diversity remain limited. Here, we used nine comparable datasets with species‐level identification of fishes from research surveys around the world to test the hypothesis that deep‐sea demersal fish assemblage composition on seamounts is consistent between major oceans. Two levels of analysis were undertaken: the first combined all presence‐absence data from a seamount, while a second more detailed analysis included catch weight data based on a smaller number of seamounts. Overall, there was a consistent separation of seamounts by region based on the compositions of their fish assemblages. New Zealand and SE Australian seamounts have a very similar ichthyofauna, which differs substantially from seamounts in the eastern South Pacific Ocean off Chile. In the North Atlantic, Bear Seamount appears to be distinct from all others, while seamount fish assemblages off Ireland, the Azores, and Faraday Seamount have some affinities. The Tasman Sea and New Caledonian seamounts show strong intra‐regional variation. On an ocean basin scale we therefore reject the hypothesis that the composition of deep‐sea demersal fish fauna is homogeneous globally. However, regional patterns of both species composition and relative abundance show some similarities between widely separated geographical locations, especially where orange roughy is a dominant species. Salinity was the main environmental factor identified in a multivariate analysis of environmental covariate data. This is likely to be a result of salinity being a key characteristic defining both Antarctic Intermediate Water and North Atlantic Deep Water, the water masses found over most seamounts examined in this study, and which may explain similarities between deep‐sea fish assemblages.

The genome of Syntrophomonas wolfei : new insights into syntrophic metabolism and biohydrogen production - Jessica R. Sieber; David R. Sims; Cliff Han; Edwin Kim; Athanasios Lykidis; Alla L. Lapidus; Erin McDonnald; Lars Rohlin; David E. Culley; Robert Gunsalus; Michael J. McInerney (Environmental Microbiology, 2010)
Summary Syntrophomonas wolfei is a specialist, evolutionarily adapted for syntrophic growth with methanogens and other hydrogen‐ and/or formate‐using microorganisms. This slow‐growing anaerobe has three putative ribosome RNA operons, each of which has 16S rRNA and 23S rRNA genes of different length and multiple 5S rRNA genes. The genome also contains 10 RNA‐directed, DNA polymerase genes. Genomic analysis shows that S. wolfei relies solely on the reduction of protons, bicarbonate or unsaturated fatty acids to re‐oxidize reduced cofactors. Syntrophomonas wolfei lacks the genes needed for aerobic or anaerobic respiration and has an exceptionally limited ability to create ion gradients. An ATP synthase and a pyrophosphatase were the only systems detected capable of creating an ion gradient. Multiple homologues for β‐oxidation genes were present even though S. wolfei uses a limited range of fatty acids from four to eight carbons in length . Syntrophomonas wolfei , other syntrophic metabolizers with completed genomic sequences, and thermophilic anaerobes known to produce high molar ratios of hydrogen from glucose have genes to produce H 2 from NADH by an electron bifurcation mechanism. Comparative genomic analysis also suggests that formate production from NADH may involve electron bifurcation. A membrane‐bound, iron–sulfur oxidoreductase found in S. wolfei and Syntrophus aciditrophicus may be uniquely involved in reverse electron transport during syntrophic fatty acid metabolism. The genome sequence of S. wolfei reveals several core reactions that may be characteristic of syntrophic fatty acid metabolism and illustrates how biological systems produce hydrogen from thermodynamically difficult reactions.

Recommendations to improve identification of hereditary and familial colorectal cancer in Europe - H. F. A. Vasen; G. Möslein; A. Alonso; S. Aretz; I. Bernstein; L. Bertario; I. Blanco; S. Bulow; J. Burn; G. Capella; C. Colas; C. Engel; et al. (Familial Cancer, 2010)

Conformational studies of peptides representing a segment of TM7 from H+-VO-ATPase in SDS micelles - Afonso M. S. Duarte; Edwin R. de Jong; Rob B. M. Koehorst; Marcus A. Hemminga (European Biophysics Journal, 2010)

Habitat structure and biological characteristics of a maerl bed off the northeastern coast of the Maltese Islands (central Mediterranean) - Marija Sciberras; Miraine Rizzo; Jael R. Mifsud; Katielena Camilleri; Joseph A. Borg; Edwin Lanfranco; Patrick J. Schembri (Marine Biodiversity, 2009)

Projected climate‐induced faunal change in the Western Hemisphere - Joshua J. Lawler; Sarah L. Shafer; Denis White; Peter Kareiva; Edwin P. Maurer; Andrew R. Blaustein; Patrick J. Bartlein (Ecology, 2009)
Climate change is predicted to be one of the greatest drivers of ecological change in the coming century. Increases in temperature over the last century have clearly been linked to shifts in species distributions. Given the magnitude of projected future climatic changes, we can expect even larger range shifts in the coming century. These changes will, in turn, alter ecological communities and the functioning of ecosystems. Despite the seriousness of predicted climate change, the uncertainty in climate‐change projections makes it difficult for conservation managers and planners to proactively respond to climate stresses. To address one aspect of this uncertainty, we identified predictions of faunal change for which a high level of consensus was exhibited by different climate models. Specifically, we assessed the potential effects of 30 coupled atmosphere–ocean general circulation model (AOGCM) future‐climate simulations on the geographic ranges of 2954 species of birds, mammals, and amphibians in the Western Hemisphere. Eighty percent of the climate projections based on a relatively low greenhouse‐gas emissions scenario result in the local loss of at least 10% of the vertebrate fauna over much of North and South America. The largest changes in fauna are predicted for the tundra, Central America, and the Andes Mountains where, assuming no dispersal constraints, specific areas are likely to experience over 90% turnover, so that faunal distributions in the future will bear little resemblance to those of today.

Characterizing Episodic Stream Acidity During Stormflows in the Great Smoky Mountains National Park - Edwin B. Deyton; John S. Schwartz; R. Bruce Robinson; Keil J. Neff; Stephen E. Moore; Matt A. Kulp (Water, Air, & Soil Pollution, 2009)

Adaptations in pre- and postsynaptic 5-HT1A receptor function and cocaine supersensitivity in serotonin transporter knockout rats - Judith R. Homberg; Sietse F. De Boer; Halfdan S. Raasø; Jocelien D. A. Olivier; Mark Verheul; Eric Ronken; Alexander R. Cools; Bart A. Ellenbroek; Anton N. M. Schoffelmeer; Louk J. M. J. Vanderschuren; Taco J. De Vries; Edwin Cuppen (Psychopharmacology, 2008)

Increased protein carbonylation in leaves of Arabidopsis and soybean in response to elevated [CO2] - Quan-Sheng Qiu; Joan L. Huber; Fitzgerald L. Booker; Vanita Jain; Andrew D. B. Leakey; Edwin L. Fiscus; Peter M. Yau; Donald R. Ort; Steven C. Huber (Photosynthesis Research, 2008)

Economics of place-based monitoring under the safe drinking water act, part II: Design and development of place-based monitoring strategies - Edwin Brands; R. Rajagopal (Environmental Monitoring and Assessment, 2008)

Economics of place-based monitoring under the safe drinking water act, part I: spatial and temporal patterns of contaminants, and design of screening strategies - Edwin Brands; R. Rajagopal (Environmental Monitoring and Assessment, 2008)

Economics of place-based monitoring under the safe drinking water act, part III: performance evaluation of place-based monitoring strategies - Edwin Brands; R. Rajagopal (Environmental Monitoring and Assessment, 2008)

Population dynamics of free-swimming Annelida in four Dutch wastewater treatment plants in relation to process characteristics - Hellen J. H. Elissen; Edwin T. H. M. Peeters; Bastian R. Buys; Abraham Klapwijk; Wim Rulkens (Hydrobiologia, 2008)

Completion of meiosis in male zebrafish (Danio rerio) despite lack of DNA mismatch repair gene mlh1 - Marcelo C. Leal; Harma Feitsma; Edwin Cuppen; Luiz R. França; Rüdiger W. Schulz (Cell and Tissue Research, 2008)

Liver lesions in demersal fishes near a large ocean outfall on the San Pedro Shelf, California - Edward Basmadjian; Edwin M. Perkins; Charles R. Phillips; Daniel J. Heilprin; Susan D. Watts; Douglas R. Diener; Mark S. Myers; Kelly A. Koerner; Michael J. Mengel; George Robertson; Jeffrey L. Armstrong; Andrew L. Lissner; et al. (Environmental Monitoring and Assessment, 2008)

Climate change scenarios for the California region - Daniel R. Cayan; Edwin P. Maurer; Michael D. Dettinger; Mary Tyree; Katharine Hayhoe (Climatic Change, 2008)

Acute and constitutive increases in central serotonin levels reduce social play behaviour in peri-adolescent rats - Judith R. Homberg; Olga J. G. Schiepers; Anton N. M. Schoffelmeer; Edwin Cuppen; Louk J. M. J. Vanderschuren (Psychopharmacology, 2007)

Quantification of single-stranded nucleic acid and oligonucleotide interactions with metal ions by affinity capillary electrophoresis: part I - Alexandra R. Stettler; Valérie Chaurin; Edwin C. Constable; Catherine E. Housecroft; Maria A. Schwarz (JBIC Journal of Biological Inorganic Chemistry, 2007)

Molecular targeting of the lymphovascular system for imaging and therapy - Heiko Schöder; Edwin C. Glass; Alain P. Pecking; Jay K. Harness; Anne M. Wallace; Peter Hirnle; Jean L. Alberini; Didier Vilain; Steven M. Larson; Carl K. Hoh; David R. Vera (Cancer and Metastasis Reviews, 2006)

Chemical Deterrence of a Marine Cyanobacterium against Sympatric and Non-sympatric Consumers - Angela Capper; Edwin Cruz-Rivera; Valerie J. Paul; Ian R. Tibbetts (Hydrobiologia, 2006)

Control of Tamarix in the Western United States: Implications for Water Salvage, Wildlife Use, and Riparian Restoration - Patrick B. Shafroth; James R. Cleverly; Tom L. Dudley; John P. Taylor; Charles VAN Riper; Edwin P. Weeks; James N. Stuart (Environmental Management, 2005)

Polymorphic microsatellite loci of Oryzomys palustris , the marsh rice rat, in South Florida detected by silver staining - Yunqiu Wang; Colin R. Hughes; Edwin A. Gines‐Candelaria; Michael S. Gaines (Molecular Ecology, 2000)

Angiotensin II-induced changes in G-protein expression and resistance of renal microvessels in young genetically hypertensive rats - Subhash J. Vyas; Christopher M. Blaschak; Mala R. Chinoy; Edwin K. Jackson (Molecular and Cellular Biochemistry, 2000)

Water and Nutrient Movement in Small, Forested Watersheds in the Boston Mountains of Arkansas - Garland L. Wheeler; Kenneth F. Steele; Edwin R. Lawson (Forest Science, 2000)
Four small (< 13.5 ha), upland, hardwood watersheds were selected for a study of the changes in water dynamics and associated chemical changes as water moves through various components of the ecosystem. These watersheds were also used to determine what changes in water movement and chemistry are related to silvicultural treatments of conversion to pine, a shelterwood cut or a clearcut applied 6 yr earlier. A fourth watershed served as a control. It was estimated that 29% of the rainfall left the watersheds. The ratio of Na+ and Cl- indicated a marine source of these elements. Enrichment from terrestrial sources was indicated for Mg+2, Ca+2, K+, and SO42-.The major changes in water movement and in water chemistry occurred between the surface of the litter layer and the bottom of the A horizon where 55% of the water and most of the nutrients that entered the watersheds were absorbed by a root network that develops at the litter A horizon interface. The degree of absorption varied from 30% for Na+ to 86% for H+. In general, nutrients that passed the A horizon also passed the E horizon and were transported out of the watersheds. SO42- was the major nutrient deposited (21.5 kg ha-1) and accumulated (15.6 kg ha-1) in the watershed followed by NO3- (9.8 and 8.2 kg ha-1) and Ca+2 (9.6 and 5.6 kg ha-1). Cl- behaved differently than other nutrients because it was stored in the canopy and surface soil layers but lost from deeper zones in the watershed. Mg+2 also differed in that it was the only nutrient to have a net loss from the watersheds.Magnesium, K+, H+, and NO3- had differences related to silvicultural treatments. Magnesium was leached from the canopy in the control and shelterwood. K+ was enriched in the throughfall of the control and possibly shelterwood. Hydrogen was absorbed in the control canopy and leached from the clearcut canopy. FOR. SCI. 46(3):335–343.

Differential Responses of Wild and Laboratory Strains of the Housefly to PCBs - Edwin H. Bryant; Joe R. Cowles (Journal of Chemical Ecology, 2000)

Monotherapy with dextromethorphan or tirilazad - but not a combination of both - improves outcome after transient focal cerebral ischemia in rats - R. Schmid-Elsaesser; Stefan Zausinger; Edwin Hungerhuber; Alexander Baethmann; Hanns-Jürgen Reulen (Experimental Brain Research, 1998)

Incomplete Eco RI digestion may lead to false diagnosis of fragile X syndrome - Katrien Storm; Ingrid Handig; Edwin Reyniers; B. A. Oostra; R. Frank Kooy; P. J. Willems (Human Genetics, 1998)

Lipid hydroperoxide-induced tumor necrosis factor (TNF)-α, vascular endothelial growth factor and neovascularization in the rabbit cornea: effect of TNF inhibition - Toshihiko Ueda; Takako Ueda; Shohei Fukuda; Richard Browne; Edwin Jenis; Robert Spengler; Richard Chou; Peter Buch; Ahmad Aljada; Paresh Dandona; R. Sasisekharan; C. Kathleen Dorey; et al. (Angiogenesis, 1997)

Effect of nitrogen supply on expression of some genes controlling storage proteins and carbohydrate synthesis in cultured maize kernels - Douglas C. Doehlert; Edwin R. Duke; Leslie J. Smith (Plant Cell, Tissue and Organ Culture (PCTOC), 1997)

Ecology in the service of biological control: the case of entomopathogenic nematodes - R. Gaugler; Edwin Lewis; Robin J. Stuart (Oecologia, 1997)

Sectional notes - Frank E. Garrett; David N. Wright; Cecil W. Frutchey; W. B. Ward; Allen Purdy; John C. Campbell; H. J. Evans; C. A. Henderson; W. C. Barnes; John Noonan; Edwin W. Cake; Claude R. Kemper; et al. (American Journal of Potato Research, 1948)

Sectional notes - Frank Garrett; A. H. Eddins; Verne C. Beverly; Marx Koehnke; John C. Campbell; H. J. Evans; W. C. Barnes; John Noonan; Edwin W. Cake; Fred J. Martin; R. E. Goodin; C. L. Fitch (American Journal of Potato Research, 1948)